Multiple Wheat Genomes Reveal Novel Gli-2 Sublocus Location and Variation of Celiac Disease Epitopes in Duplicated α-Gliadin Genes - Halstead-Nussloch, Gwyneth; Tanaka, Tsuyoshi; Copetti, Dario; Paape, Timothy; Kobayashi, Fuminori; Hatakeyama, Masaomi; Kanamori, Hiroyuki; Wu, Jianzhong; Mascher, Martin; Kawaura, Kanako; Shimizu, Kentaro K.; Handa, Hirokazu (Frontiers in Plant Science, 2021)
The seed protein α-gliadin is a major component of wheat flour and causes gluten-related diseases. However, due to the complexity of this multigene family with a genome structure composed of dozens of copies derived from tandem and genome duplications, little was known about the variation between accessions, and thus little effort has been made to explicitly target α-gliadin for bread wheat breeding. Here we analyzed genomic variation in α-gliadins across 11 recently published chromosome-scale assemblies of hexaploid wheat, with validation using long-read data. We unexpectedly found that the Gli-B2 locus is not a single contiguous locus but is composed of two subloci, suggesting the possibility of recombination between the two during breeding. We confirmed that the number of immunogenic epitopes among 11 accessions varied. The D subgenome of a European spelt line also contained epitopes, in agreement with its hybridization history. Evolutionary analysis identified amino acids under diversifying selection, suggesting their functional importance. The analysis opens the way for improved grain quality and safety through wheat breeding.